Collaborative Management Between Islamic Educational Institutions and Community Health Centers (Puskesmas) in Health Promotion: A Case Study in Pace District, Nganjuk Regency - Syaiful Muda'i (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2025)
This Study addresses the issue of fragmented health services in rural Indonesia, which hampers effective health promotion efforts. The collaboration between Islamic educational institutions, such as madrasahs and pesantrens, and Puskesmas represents an untapped resource for enhancing community health outcomes. The study aims to analyze the models of collaborative management utilized in Pace District to promote health through this partnership. It employs a qualitative case study approach involving interviews, focus group discussions (FGDs), and document analysis with 35 participants, including school principals, health workers, and community leaders, ensuring a comprehensive understanding of stakeholder perspectives. Key findings reveal that formalized partnerships based on memorandums of understanding (MOUs) have successfully improved vaccination coverage and nutrition education, demonstrating the potential of institutional collaboration in extending public health reach. However, challenges such as resource asymmetry—where one party has more assets or capacity than the other—and bureaucratic inertia slow the pace and efficiency of joint efforts. The study concludes that Islamic educational institutions significantly amplify the outreach capabilities of Puskesmas, but the success of these collaborations depends heavily on trust-building between the parties and structured coordination mechanisms to overcome administrative hurdles. This research highlights that fostering collaborative health promotion between religious education and public health sectors in rural Indonesia can address service fragmentation, leveraging the social capital and religious authority of Islamic institutions to support government health initiatives effectively. Building on this model may enhance sustainable health improvements in similar contexts with shared cultural and institutional characteristics.